ENGLISH-INVESTIGATING THE RELIGIOUS AND SOCIAL SERVICES OF JAMIA IRSHAD ULOOM MAREK: A CRITICAL REVIEW - Zain- ul- Abdin Arijo; Muhammad Majid (دی اسکالر)
Madrasas, traditionally known as centers of Islamic learning and play a pivotal role in educating and shaping the religious and social fabric of Muslim communities around the world. This critical analysis examines the dual role of madrasas in providing religious education and fostering social services within their communities. This research begins by delineating the historical foundations of madrasa and its adaptation in contemporary contexts. It scrutinizes the pedagogical methods employed in religious education, assessing their efficacy in transmitting Islamic teachings while addressing modern educational standards. Furthermore, this study evaluates the extent to which Jamia Irshad Uloom Marek engaged in social services, including educational services, publication services, preaching services, social services and political services. This research also explored the services of some important Ulemas, Qaris and Hafiz Quran who educated from the institution of Jamia Irshad Uloom Marek and their services. Besides, this study also provides and insight into critical analysis of curriculum standard and critical analysis of the social and religious services given by Jamia Irshad Uloom Marek. Through a synthesis of descriptive analysis seeks to offer insights into the transformative potential of Jamia Irshad Uloom Marek beyond religious education, highlighting their role as catalysts for social cohesion and communal well-being. This study aims to inform policymakers, educators, and religious leaders on strategies to enhance the holistic contributions of madrasas to their communities in the 21st century in general and Jamia Irshad Uloom Marek in particular. The findings of this research suggests that the foundation of Jamia Irshad Uloom Merik was laid in 1953 by Wali Kamil Qutb-ul-Aqtab, Imam Awaliya Hazrat Maulana Sayyin Hamdullah Halejawi. Jamia Irshad al-Uloom Marek has a professional and religious relationship with the Sunni Hanafi Deobandi Ahl-e-Sunnah Wal-Jamaat from the foundation of the madrasa until today. The findings of this study further pinpoint that this institution has been a hub of Islamic teaching and produced number of Ulemas, Qaris, and Hafiz Quran in the region as a whole.